Produtividade da mão de obra na execução de alvenaria estrutural com blocos de concreto - Carvalho, Ana Beatriz Luna de (2013)
Over the last years the growth of construction industry in Brazil always presented itself above national ratings, in this way, the construction industry has been continually searching for reflecting innovations in rationalizing of their systems, methods and construction processes. Construction companies that properly use their resources provide products at lower costs to the market. This paper seeks to conceptualize the structural masonry, as constructive method, detailing its components and construction stages, showing the importance of managinga venture of structural masonry, integrating all sectors such as design, planning, production control, logistics and execution. Still it seeks to mesure the productivity ratings of the labor on the works studied, identifying the main parameters that influence this productivity. It was sought to know the productivity ratings of constructions of structural masonry, through professionals involved, their level of qualification and training, machines and equipments used, the effect of the choice of modular dimension. For the realization of this paper were chosen four constructions of structural masonry in a construction company, in the city of Fortaleza, the characteristics of the ventures are similar relating to the project so there were a greater uniformity of information. This study Obtained data that reflects the productivity ratings of companies in the region and identified the main factors that influence this productivity.